RItA: The Italian severe/uncontrolled asthma registry. Issue 3 (22nd November 2017) - Maio, S.; Baldacci, S.; Bresciani, M.; Simoni, M.; Latorre, M.; Murgia, N.; Spinozzi, F.; Braschi, M.; Antonicelli, L.; Brunetto, B.; Iacovacci, P.; Roazzi, P.; et al.
Abstract: Background: The Italian severe/uncontrolled asthma (SUA) web‐based registry encompasses demographic, clinical, functional, and inflammatory data; it aims to raise SUA awareness, identifying specific phenotypes and promoting optimal care. Methods: Four hundred and ninety three adult patients from 27 Italian centers (recruited in 2011‐2014) were analyzed. Results: Mean age was 53.8 years. SUA patients were more frequently female (60.6%), with allergic asthma (83.1%). About 30% showed late onset of asthma diagnosis/symptoms (>40 years); the mean age for asthma symptoms onset was 30.2 years and for asthma diagnosis 34.4 years. 97.1% used ICS (dose 2000 BDP), 93.6% LABA in association with ICS, 53.3% LTRAs, 64.1% anti‐IgE, 10.7% theophylline, and 16.0% oral corticosteroids. Mean FEV1 % pred of 75.1%, median values of 300/mm 3 of blood eosinophil count, 323 kU/L of serum total IgE, and 24 ppb of FENO were shown. Most common comorbidities were allergic rhinitis (62.4%), gastroesophageal reflux (42.1%), sinusitis (37.9%), nasal polyposis (30.2%), and allergic conjunctivitis (30.2%). 55.7% of SUA patients had exacerbations in the last 12 months, 9.7% emergency department visits, and 7.3% hospitalizations. Factors associated with exacerbation risk were obesity (OR, 95% CI 2.46, 1.11‐5.41), psychic disorders (2.87, 0.89‐9.30—borderline), nasal polyps (1.86, 0.88‐3.89—borderline), partial/poor asthma treatment adherence (2.54, 0.97‐6.67—borderline), and anti‐IgE use in a protective way (0.26, 0.12‐0.53). Comparisons to severe asthma multicenter studies and available registries showed data consistency across European and American populations. Conclusions: An international effort in the implementation of SUA patients' registries could help to better understand the clinical features and to manage severe asthma, representing a non‐negligible socioeconomic burden for health services.